The Ability of Mexican Sword Plant (Echinodorus palaefolius) as Copper (Cu) Phytoremediator - Lorensia, Rantika Eka; Rachmadiarti, Fida (LenteraBio : Berkala Ilmiah Biologi, 2024)
Water pollution can come from inorganic pollutants like copper (Cu). Copper in high concentrations will cause toxic effects, so water quality treatment efforts are needed. Phytoremediation can be used to treat water polluted with heavy metals whose use will support the Sustainable Development Goals (SDGs). One plant with potential as a phytoremediator is mexican sword plant (Echinodorus palaefolius). This study aims to describe the ability of Echinodorus palaefolius as a phytoremediation agent to reduce Cu levels in the growing media, describe the effect of variations in Cu concentration on leaf chlorophyll levels and wet biomass. Data were analyzed using the SPSS one-way ANOVA test followed by the Duncan test. Analysis of supporting data in the form of pH and water temperature was done descriptively quantitative. The results showed that the ability of E. palaefolius to absorb Cu metal in the planting media, leaf chlorophyll content, and wet biomass was influenced by Cu concentration. The higher the concentration of Cu in the growing media, the greater the absorption of Cu by E. palaefolius, the lower the leaf chlorophyll content, and the increase in wet biomass. The results of this study prove that Echinodorus palaefolius can absorb Cu metal.